Study of Mechanical and Wear Properties of Stir-Cast Al-Si-Cu alloy - Divakaran Namboodiri, Dileep; Ilangovan, S (International Journal of Engineering and Technology, 2018)
The present work deal with an investigation of the mechanical and wear properties of eutectic Al-12.8%Si-2.5%Cu under as cast and homogenized conditions. The alloy was melted in a ceramic crucible, stirred and gravity poured into a metal mold and was then cooled under atmosphere. The stirring parameters include a stirrer speed of 400rpm at a melt temperature of 7500C for about 10 minutes. The cast specimens were homogenized in a nitrogen atmosphere crucible at a temperature of 3500C for 8 hours and furnace cooled to room temperature. The microstructure of as cast and homogenized specimen were studied under SEM. The results of SEM study showed that the Si particles were more evenly dispersed around the a-Al matrix after homogenization. This even dispersion of Si particles led to an increase in the hardness and ultimate tensile strength of the alloy. The dry sliding wear behavior was studied using a pin-on-disc machine. It is seen that the wear rate reduced with increase in sliding speed. The EDAX analysis of worn surface showed the phenomenon of lamination. It is concluded that the oxide layer formation was also a reason for increase in wear resistance of the material.Â Â